The Gravitational-wave Optical Transient Observer (GOTO): Prototype performance and prospects for transient science - Steeghs D.; Galloway D.K.; Ackley K.; Dyer M.J.; Lyman J.; Ulaczyk K.; Cutter R.; Mong Y.L.; Dhillon V.; O'Brien P.; Ramsay G.; Poshyachinda S.; et al. (Oxford University Press, 2025)
The Gravitational-wave Optical Transient Observer (GOTO) is an array of wide-field optical telescopes, designed to exploit new discoveries from the next generation of gravitational wave detectors (LIGO, Virgo, and KAGRA), study rapidly evolving transients, and exploit multimessenger opportunities arising from neutrino and very high energy gamma-ray triggers. In addition to a rapid response mode, the array will also perform a sensitive, all-sky transient survey with few day cadence. The facility features a novel, modular design with multiple 40-cm wide-field reflectors on a single mount. In 2017 June, the GOTO collaboration deployed the initial project prototype, with 4 telescope units, at the Roque de los Muchachos Observatory (ORM), La Palma, Canary Islands. Here, we describe the deployment, commissioning, and performance of the prototype hardware, and discuss the impact of these findings on the final GOTO design. We also offer an initial assessment of the science prospects for the full GOTO facility that employs 32 telescope units across two sites.